2018
DOI: 10.1186/s12936-018-2479-y
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of submicroscopic Plasmodium falciparum gametocyte carriage and multiplicity of infection in children, pregnant women and adults in a low malaria transmission area in Southern Ghana

Abstract: BackgroundThe gametocyte stage of Plasmodium falciparum is considered an important target for disrupting malaria transmission. Indications are that various demographic groups, such as children and pregnant women may differ in risk of harbouring gametocytes, which may be crucial for targeted control. In this study, the relationship between the prevalence and multiplicity of P. falciparum, asexual parasite infections and gametocytaemia was assessed in three different demographic groups in an area of southern Gha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
71
2
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(83 citation statements)
references
References 54 publications
5
71
2
5
Order By: Relevance
“…The absence of variation in gametocyte carriage across the dry and rainy season in Asutsuare is supportive of the very low year-round malaria transmission recorded in Asutsuare. The low gametocyte prevalence identified in the participants from Asutsuare supports a recent report that identified low gametocyte prevalence amongst children and adults, including pregnant women in Asutsuare [34].…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The absence of variation in gametocyte carriage across the dry and rainy season in Asutsuare is supportive of the very low year-round malaria transmission recorded in Asutsuare. The low gametocyte prevalence identified in the participants from Asutsuare supports a recent report that identified low gametocyte prevalence amongst children and adults, including pregnant women in Asutsuare [34].…”
Section: Discussionsupporting
confidence: 84%
“…As anticipated, the prevalence of asymptomatic carriers was significantly higher in Obom, the high parasite prevalence setting, than in Asutsuare where P. falciparum parasite prevalence has been reported to be very low for over a decade [34,36]. No significant difference was observed in asexual parasite carriage between the dry and rainy season in Asutsuare, mainly because malaria is low and perennial [36] and supports an earlier report on asexual parasite prevalence in another low malaria parasite intensity setting of Ghana [40].…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Based on the central role of gametocytes in propagating and sustaining malaria transmission, the prevalence of gametocytes is largely used as a parameter of the disease transmission [11,12]. Studies in malaria endemic and high transmission areas have reported high asexual parasite and gametocyte prevalence and densities in children relative to adults [13,14]. In such high malaria transmission settings, due to repeated parasite exposure, older children and adults develop immunity against the parasite [15,16].…”
mentioning
confidence: 99%
“…In such high malaria transmission settings, due to repeated parasite exposure, older children and adults develop immunity against the parasite [15,16]. As a result, this category of people are most likely to experience asymptomatic infections harbouring gametocytes at microscopic and sub-microscopic densities thereby serving as efficient parasite reservoirs for sustaining malaria transmission [12,14,17].…”
mentioning
confidence: 99%